Capp Street Project 1991-1993 : Capp Street Project supports multidisciplinary work by local, national, and international artists while expanding the Capp Street : experimental projects exhibitions and a public archive on installation art - Dialogue around contemporary art through related forums, workshops and lectures. - Blumberg, Linda; Bolton, Richard; Ceruti, Mary; Chin, Mel; Creativity, Explored; Goto, Reiko; Hatch, Ann; Lewallen, Constance; Luna, James; Olabarria, Pilar; Pineda, Eduardo; Seid, Steve; et al. (San Francisco : Capp Street Project/AVT, 1993)
Alavi, Seyed ; Awol ; Babcock, Jo ; Baden, Mowry ; Bell, Michael S. ; Bolton, Richard ; Cheang, Shu Lea ; Chin, Mel ; Ericson, Kate ; Goto, Reiko ; Haigood, Joanna ; Harvey, Laury ; Henry, Caryl ; Lang, Julian ; Luna, James ; Olabarria, Pilar ; Pineda, Eduardo ; Shum, Hilda ; Simpson, Buster ; Stone, George ; Suderburg, Erika ; Sun, May ; Suzanne Kanatsiz and creativity explored ; Templeton, Fiona ; Townsend, Landa ; Tsinhnarjinnie, Hulleah ; Weinger, Lauren ; Wilson, Fred ; Wong, Flo ; Ziegler, Mel
biografie
Engels
boek